COVID-19 vaccine antibody responses in community-dwelling adults to 48 weeks post primary vaccine series - Sharon L. Walmsley; Leah Szadkowski; Bradly Wouters; Rosemarie Clarke; Karen Colwill; Paula Rochon; Michael Brudno; Rizanni Ravindran; Janet Raboud; Allison McGeer; Amit Oza; Christopher Graham; et al. (iScience, 2023)
Summary: We report a decentralized prospective cohort study of self-reported adverse events and antibody responses to COVID vaccines derived from dried blood spots. Data are presented for 911 older (aged >70 years) and 375 younger (30–50 years) recruits to 48 weeks after the primary vaccine series. After a single vaccine, 83% younger and 45% older participants had overall seropositivity (p < 0.0001) increasing to 100/98% with the second dose, respectively (p = 0.084). A cancer diagnosis (p = 0.009), no mRNA-1273 vaccine doses (p <0 .0001), and older age (p <0 .0001) predicted lower responses. Antibody levels declined in both cohorts at 12 and 24 weeks increasing with booster doses. At 48 weeks, for participants with 3 vaccine doses, the median antibody levels were higher in the older cohort (p = 0.04) with any dose of mRNA-1273 (p <0 .0001) and with COVID infection (p <0 .001). The vaccines were well tolerated. Breakthrough COVID infections were uncommon (16% older cohort, 29% younger cohort; p < 0.0001) and mild.